Recycled tetrahedron-like CuCl from waste Cu scraps for lithium ion battery anode. (July 2017) - Hou, Hongying; Yao, Yuan; Liu, Song; Duan, Jixiang; Liao, Qishu; Yu, Chengyi; Li, Dongdong; Dai, Zhipeng
Highlights: High EVA CuCl was recycled with 88.7% recovery from waste Cu craps. The recycled CuCl displayed regular tetrahedron-like morphology. The evolution mechanism of the recycled CuCl crystal was proposed. The corresponding discharge capacity in LIB was 171.8 mAh/g after 50 cycles. The results shed a new light on resource recovery and environmental protection. Abstract: The wide applications of metal Cu inevitably resulted in a large quantity of waste Cu materials. In order to recover the useful Cu under the mild conditions and reduce the environmental emission, waste Cu scraps were recycled in the form of CuCl powders with high economic value added (EVA) via the facile hydrothermal route. The recycled CuCl powders were characterized in terms of scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD). The results suggested that the recycled CuCl powders consisted of many regular tetrahedron-like micro-particles. Furthermore, in order to reduce the cost of lithium ion battery (LIB) anode and build the connection of waste Cu scraps and LIB, the recycled CuCl powders were evaluated as the anode active material of LIB. As expected, the reversible discharge capacity was about 171.8 mAh/g at 2.0 C even after 50 cycles, implying the satisfactory cycle stability. Clearly, the satisfactory results may open a new avenue to develop the circular economy and the sustainable energy industry, which would be very important in terms of both the resource recovery and the environmental protection.